การเปรียบเทียบภาพลักษณ์ตราสินค้าของเครื่องสำอางเกาหลีกับเครื่องสำอางไทย - กัณฐชา ไกรสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objectives of this research are (1) to study brand image of Korean and Thai cosmetics for actual image (2) to study comparison of Korean and Thai cosmetics brand image the in Thailand and (3) to study correlation between brand image with consumer’s perceptions . This research can be divided into 2 parts. Part 1 is a qualitative research. The data in use from interview the administrator or who responsibility for public relations include collected documents articles, and relevant researches. Part 2 is a survey research collecting from questionnaire by 400 female who live in Bangkok area and know both Korean and Thai cosmetics. Therefore, statistics used in this research are frequency, percentage, mean scores, standard deviation and F-Test. SPSS program is employed for data processing. The results of this study are (1) The results are ETUDE cosmetic communication channel through consumers is from ordinary woman’s appearance to a princess beauty like concept. Whereas for SKINFOOD cosmetic communication process is by informing the consumers that their products are food for skin and are made from natural materials. Oriental Princess cosmetic communication concept is the use of natural products that their cosmetics are made from. And while SHEENE cosmetic communication concept to creates a key massage of their product, which makes consumers remember it easily. This concept goes along with other public relations media such as; Mass Media, Personal Media, Publications and Electronic Media. (2) The results are the respondents are more familiar with the Thai cosmetics logo brands more than Korean cosmetic brands. The respondents remember activities and sponsored television program of Thai cosmetic brands more than Korean cosmetic brands. The respondents express more opinions to perception or activity for marketing public relations of Thai cosmetic brands more than Korean cosmetic brands. The respondents are able to express more opinions to products of Thai cosmetic brand than Korean cosmetic brand. And the respondents express opinions to personality of products of Thai cosmetic brand more than Korean cosmetic brand.